ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN KEHAMILAN REMAJA - Atika, Atika; Sa’adi, Ashon; Wittiarika, Ivon Diah (Poltekkes Kemenkes Pontianak, 2024)
Background: Adolescence is a transition from children to adulthood, where changes occur, namely physical or biological changes and psychological changes, this will cause turmoil in every teenager which causes deviant behavior, for example uncontrolled sexual behavior resulting in teenage pregnancy. The purpose of this study was to analyze the factors associated with teenage pregnancy in Sumberanyar Village, Wongsorejo District, Banyuwangi Regency in 2023. Method: quantitative research using a cross sectional design. The sample was adolescents who were pregnant, adolescents who were notpregnant, adolescents who had given birth, and adolescents who had been pregnant, taken by using nonprobality sampling in the form of purposive sampling with a total of 69 respondents. The research data were analyzed using the Chi Square test. Results: The results of the Chi Square test show that the factors that are significantly associated with teenage pregnancy are adolescent knowledge (p=0.007), attitudes towards teenage pregnancy (p=0.005), the role of parents (p=0.006) while the role of peers (p=0.224) is a factor that is not associated with the incidence of teenage pregnancy.